We're all wonders - Palacio, R. J. (New York Alfred A. Knopf, 2017)
Augie enjoys the company of his dog, Daisy, and using his imagination, but painfully endures the taunts of his peers because of his facial deformity.
"A Borzoi book."
Keywords: Abnormalities, Human -- Juvenile fiction; Self-acceptance -- Juvenile fiction; Teasing -- Juvenile fiction; Dogs -- Juvenile fiction; Abnormalities, Human -- Fiction; Self-acceptance -- Fiction; Teasing -- Fiction; Dogs -- Fiction; Birth defects -- Fiction; Self-acceptance -- Fiction; Teasing -- Fiction; Dogs -- Fiction